SWOT Analysis in Implementation of Health Protocols on Food Handlers for Covid-19 Prevention in Taman Prestasi, Surabaya City Culinary Center in 2021 - Mayangsari Yunika Wijaya; Rusmiati Rusmiati; Narwati Narwati (International Journal of Advanced Health Science and Technology, 2022)
The role of food handlers is to break the chain of transmission of Covid-19 by obediently implementing health protocols in places to eat. Objective: analyze the implementation of food-tailoring health protocols for the prevention of Covid-19 in the Culinary Center of Taman Prestasi Kota Surabaya. Analyze the implementation of food-tailoring health protocols for the prevention of Covid-19 in the Culinary Center of Taman Prestasi Kota Surabaya. This study is a descriptive observational study of a cross-sectional approach with SWOT analysis methods that are observed at the same time. The population of this study is food snatchers in the Culinary Center of Surabaya City Taman Prestasi. Food handlers in the culinary center of the most Taman Prestasi s are between 41-50 years old and female. Most high school-educated food vendors with a working period of between 1-5 years. Compliance of food handlers in the implementation of health protocols in the Culinary Center of Surabaya City Taman Prestasi with compliant criteria there are 19 (45%), and with non-compliant criteria, there are 23 (55%). Facilities and infrastructure in The Culinary Center of Taman Prestasi Surabaya City include criteria available in the application of health protocols with a percentage of 62%. The analysis of the implementation of food-enhancing health protocols with SWOT methods has quadrant I (progressive) criteria explaining the position of the Culinary Center of Surabaya City Taman Prestasi is strong and has the opportunity to develop efforts to prevent Covid-19 transmission by increasing the implementation of health protocols. Business actors routinely monitor and maintain the facilities and infrastructure available in the implementation of health protocols.